FUNGSI HUKUM DALAM PERUMUSAN ANGGARAN PENDAPATAN DAN BELANJA DESA MELALUI BADAN PERMUSYAWARATAN DESA - Sutrisno, Endang; Artadi, Ibnu; Khafdilah, Khafdilah; Widianti, Hesti (Universitas Wiralodra, 2020)
Village Consultative Agency (BPD - Badan Permusyawarat Desa) in implementing its function as a bridge connecting the village head with the village community must also carry out its main function as the representative. The problem arises is how does the legal order set issue of the Village Consultative Agency (BPD) on the perspective of the formulation of Village Revenues and Expenditures Budget (APBDes - Anggaran Pendapatan dan Belanja Desa) based on the legal basis of Government Regulation No. 72 of 2005 concerning the village. The next problem arises is what are the obstacles faced by the Village Consultative Agency (BPD) in carrying out its duties to prepare the Village Revenues and Expenditures Budget (APBDes). The process of formulating the Village Regulation has been carried out through the correct stages and in accordance with Law Number 6 of 2014 Jo Government Regulation Number 43 of 2014 concerning Jo Village Domestic Ministerial Regulation Number 111 of 2016 concerning Technical Guidelines for Regulations in the Village, namely through initiation, socio-political and juridical stages.